ANALISIS PENAMBAHAN PIPA DISTRIBUSI AIR BERSIH PADA JEMBATAN DIATAS SUNGAI BATEE ILIEK SAMALANGA BIREUEN - Mohammad Imamuddin Imam; Mukhibullah (Jurnal Infrastruktur, 2019)
In 2018 in order to service coverage krueng peusangan PDAM clean water district bireuen cost in the branches in samalanga there are no optimal of the population lives in samalanga 31.203 /, 6442 households as well as problems passing on the existing bridge a river bate ilieik long 37.5 m. until the leak happened corrosionIn meet the water needs review on a crossing a river by taking into account the analysis lose water (loss head), dimensions pipe the discharge, the pressure pipe in the flow in a pipe and also the pipe. Structure From the analysis of this research are dimensions: diameter pipe taken was, 200 mm discharge flow on 4500 families is 35.94 ltr / seconds. The total loss energy secondary head on pipelines is 44.04 m meanwhile lost energy and water loss energy ( head ) Secondary losses and minor losses dijembatan is: 0.48 meters or 1.09 % and also rest pressure swept obtained 1.48 bar still satisfying the minimum requirements pipe distribution sni 7509: 2011 is 1 bar so system technically capable of distributes water in, gravity for the addition of a pipe at river bridge analysis structure able to the addition of a pipe